Spiritual Care in Palliative Care: A Physician’s Perspective - Gijsberts, Marie-José H. E. (Religions, 2022)
Palliative care is defined as ‘an approach that improves the quality of life of patients and their families who are facing problems associated with life-threatening illness. It prevents and relieves suffering through identification, assessment and treatment of pain and other problems, whether physical, psychosocial or spiritual’. As a palliative care physician, I aim to explore and meet the needs of my patients and their loved ones. As I am specifically trained as a specialist in assessing and treating ‘pain and other physical symptoms’, in psychological, social and spiritual issues, I am a generalist. Two approaches are described to assess spiritual needs in palliative care: The first is adjoining the analytic concept of the four dimensions of palliative care: using an instrument, measuring spiritual well-being or spiritual needs, and measuring the quality of life, with specific attention to spiritual issues. Second, a holistic approach is promoted, with openness to the patients’ narrative of their life, disease and suffering. In the integrity of the clinical encounter, medical, ethical and spiritual issues may be discussed. Broadening our clinical language with ethical, psychosocial, and spiritual vocabulary is mandatory, and self-reflection, interdisciplinary collaboration and specific interdisciplinary training may be supportive to develop such a clinical language.